QRIS Implementation in Muslim MSMEs: Opportunities and Challenges for Digital Financial Inclusion in Pamekasan - Khotibul Umam; Umarul Faruq; Syahda Adita; Nadya Apriza Azizi; Halimi Husayn (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: This study examines the opportunities and challenges of implementing the Quick Response Code Indonesian Standard (QRIS) to strengthen digital financial inclusion among Muslim micro, small, and medium enterprises (MSMEs) in Pamekasan Regency, Indonesia. Although QRIS adoption has increased nationally, its implementation in socio-religious regions remains uneven due to differences in digital literacy, technological readiness, and trust in digital financial systems. This study integrates the Technology Acceptance Model (TAM), Unified Theory of Acceptance and Use of Technology (UTAUT), and Islamic business ethics to analyze technology acceptance among Muslim MSMEs. Method: Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and documentation involving 21 participants selected through purposive sampling. The data were analyzed thematically using the Miles and Huberman interactive model. Results: The findings reveal that QRIS enhances transaction efficiency, financial transparency, and access to digital financial services among Muslim MSMEs. Islamic ethical values, including amanah, ṣidq, taysīr, and maṣlaḥah, strengthen trust and acceptance toward digital payment systems. However, QRIS implementation continues to face challenges, including limited digital literacy, cybersecurity concerns, infrastructure instability, settlement delays, and resistance to cashless transactions. Conclusion: This study contributes to the literature by demonstrating that technology acceptance among Muslim MSMEs is shaped not only by perceived usefulness and ease of use but also by socio-religious values and ethical considerations. The findings highlight the importance of integrating digital literacy programs, institutional support, and Islamic ethical approaches to promote inclusive and sustainable digital financial ecosystems.